The medium‐term impacts of integrated crop–livestock systems on crop yield and economic performance. (14th November 2021) - Rai, Teerath Singh; Nleya, Thandiwe; Kumar, Sandeep; Sexton, Peter; Wang, Tong; Fan, Yubing
Abstract: Integrated crop–livestock (ICL) systems are diverse production systems that can improve resource utilization through spatially or temporally rotating land among crop, livestock, and pasture uses. However, research on whether the enhanced resource utilization translates to greater crop productivity is still warranted. A field experiment was initiated at South Dakota State University in 2016 to determine the impacts of integrating cover crops and livestock grazing into a crop rotation of oat ( Avena sativa L.)–maize ( Zea mays L.)–soybean [ Glycine max (L.) Merr.]. The objectives were to (a) determine the medium‐term (4–6 yr) impacts of cover crops and livestock grazing on crop performance, and (b) determine the economic impacts of integrating cover crops and livestock grazing. Treatments included (a) a cover crop blend planted after oat harvesting (CC), (b) a CC blend that was the same as in (a) but with grazing of the CC and crop residue in late fall (ICL), and (c) a control treatment without any CC or livestock grazing. The results showed that planting cover crops, with or without grazing, did not impact the subsequent crop yield. Maize yield decreased by 17.7% in a dry year in 2017 in the CC treatment compared with the control; however, the difference was nonsignificant ( P  = .06). Economic analysis showed that the net revenue generated by the ICL system could compensate for the additional costs incurred by integrating cover crops into the crop production system. Core Ideas: Integrating cover crops in the rotation did not reduce the yields of succeeding crops. Fall grazing of cover crops did not have any negative impact on crop productivity. Maize was sensitive to soil water depletion caused by cover crops. Grazing cover crops and crop stubble enhanced net returns.